FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PEKERJA KONSTRUKSI PROYEK PEMBANGUNAN 6 RUAS TOL DALAM KOTA JAKARTA SEKSI 1A KSO JAYA KONSTRUKSI-ADHI TAHUN 2020 - Jevitha Prameswari (2021)
Work fatigue is a condition characterized by decreased energy during work activities. Work fatigue can negatively affect worker performance, company's production, and work accidents. Various factors that contributed to work fatigue are individual, work, and environmental factors. Workers working on toll road construction projects may be at risk of work fatigue. This study aims to find out the factors related to work fatigue in construction workers of project 6 Inner-City Toll Road Segments in Jakarta Section 1A KSO Jaya Konstruksi-Adhi. This research type is quantitative. The design of this study was cross-sectional with 100 construction workers selected using purposive sampling techniques. The research instruments used were a questionnaire, pulse oximeter, and heat stress meter. The bivariate analysis result with chi-square test showed that there is a relationship between age (p=0.004), marital status (p=0.023), work duration (p=0.030), mental workload (p=0.001), and physical workload (p=0.000) with work fatigue, while the working climate (p=0.557) has no relationship with work fatigue. The multivariate analysis result with logistic regression showed that variable physical workloads become the most dominant variables affecting work fatigue with POR=4,3 (95% CI: 1,5-11,9). Workers are advised to optimize rest time, drink more mineral water, and doing exercise between work.